Մակերիկամների ֆունկցիոնալ ակտիվության փոփոխության ժամանակ կլինիկական ախտանիշների դիտարկում - Ն. Բ. Բեգլարյան (Հայաստանի ԳԱԱ)
В настоящее время есть множество научных работ, связанных с органическими патологиями надпочечников. Вместе с этим функциональные расстройства надпочечников малоизучены. Встречаются работы по функциональному гиперкортицизму, также работы, где говорится о так называемом синдроме усталых надпочечников. А ведь еще Г. Селье очень подробно описал функциональные перестройки в надпочечниках, когда они подвергаются длительному стрессу.The issue of adrenals organopathology has been widely covered by many research papers unlike the functional disorders of adrenals that are understudied for now. There are some articles regarding the functional hypercorticism and some researches were made on the so-called “Adrenal Fatigue Syndrome”. Meanwhile it is a well-known fact that it was H.Selye who described the functional alterations in adrenals caused by a lasting stress.
Keywords: Physiology; Medicine; Pathology